Technical implications of a novel deep learning system in the segmentation and evaluation of computed tomography angiography before transcatheter aortic valve replacement - Min Jin; Yu Mao; Jian Yang; Jian Liu; Guozhong Chen; Timothée Noterdaeme; Rüdiger Lange; Chenming Ma; Yingqiang Guo; Haibo Zhang (Therapeutic Advances in Cardiovascular Disease)
Objective: The goal of this study was to compare the computed tomography angiography scans of the segmentation results from the Cvpilot, 3mensio, and Volume Viewer systems to explore the practicability of the Cvpilot system in the automatic segmentation and technical evaluation of the aortic root before transcatheter aortic valve replacement (TAVR). Design: A total of 154 patients who underwent TAVR at our center from January 2022 to May 2023 were enrolled, and their computed tomography angiography images were analyzed using the Cvpilot, 3mensio, and Volume Viewer systems, respectively. Setting: Not applicable. Participants: Not applicable. Main outcome measures: The reconstructed computed tomography angiography images were evaluated by experts, and the measurements of the aortic roots were analyzed statistically. Results: Compared with the 3mensio system, 92.2% of patients ( n  = 142) evaluated with the Cvpilot system reached grade A, 5.2% of patients ( n  = 8) reached grade B, and 2.6% of patients ( n  = 4) reached grade C. Compared with the Volume Viewer system, 90.9% of patients ( n  = 140) evaluated with the Cvpilot system achieved grade A, 7.1% of patients ( n  = 11) achieved grade B, and 2.0% of patients ( n  = 3) achieved grade C. Furthermore, there was no significant difference among the measurement results of the Cvpilot, 3mensio, and Volume Viewer systems (all p  > 0.05). Conclusion: Overall, the Cvpilot system is effective and reliable. It can accurately complete the segmentation and the measurement of aortic root structures, thereby effectively improving the measurement quality before TAVR. Trial registration: Not applicable.